DI-GEP: A New Lifetime Extending Algorithm for Target Tracking in Wireless Sensor Networks - Shucheng Dai; Chuan Li; Chun Chen (International Journal of Distributed Sensor Networks)
Wireless sensor networks (WSNs) are widely used in detecting, locating, and tracking moving objects. The cheap, low-powered, and energy-limited sensors that are set up in large areas may consume large portion of energy and disable the whole network. In this paper, a new energy-efficient method based on Distributed Incremental Gene Expression Programming (DI-GEP) is proposed to collaboratively mine moving patterns of moving targets in order to turn on/off some sensor nodes at certain time to save energy further. Meanwhile, an adjustable sliding window is designed to quickly train the latest collected location data in order to improve the efficiency of DI-GEP. The simulation results show that the proposed method effectively prolongs the network lifetime by around 25% compared with the EKF and ECPA.